Treatment of refractory simple partial status epilepticus by the addition of oral lacosamide in neurosurgical patients. Report of 3 cases() - Hadjigeorgiou, Georgios F. (Elsevier, 2013)
Lacosamide is a new antiepileptic drug that has been successfully used for the treatment of partial seizures. We report three neurosurgical cases of simple partial status epilepticus refractory to multiple antiepileptic medications. The addition of oral lacosamide in doses of 200–400 mg in combination with the existing treatment had successfully controlled the seizures within four days.